NITRIC OXIDE – A BIOMARKER OF THE PROGRESS AND METASTASIS OF RENAL CELL CANCER INTO THE BRAIN - Komarevtsev, V.N.; Balabanova, K.V.; Kalinin, I.V.; Usatov, S.A.; Ovcharenko, M.O.; Komarevtseva, I.O.; Zielonyi, I.I. (World of Medicine and Biology, 2024)
Endogenous nitric oxide plays a pivotal role in cancer development. The purpose of the study was to investigate the role of the biomarker of nitric oxide metabolites in the progression and metastasis of renal cell carcinoma to the brain. To test our hypothesis, this case-control study consisted of the indicators of nitric oxide metabolites in the inactive parenchyma resected during operations for urolithiasis (the comparison group, n=13); 103 patients with renal cell carcinoma. To analyze the metabolites of nitric oxide, we used a technique that allows us to determine the content of nitrite and nitrate ions in the same sample. The content of stable metabolites of nitric oxide was expressed in μg/mg protein in tissues. Levels of nitric oxide metabolites were significantly higher (1.5-fold higher) in tumor tissue than in peri-tumor tissue. Nitric oxide exhibits a pro- or antitumorigenic effect depending on the level of NO and the stage of the tumor process. The level of nitric oxide in tumor tissue was an independent predictor of renal cell carcinoma progression and its metastasis to the brain. The content of nitric oxide in peri-tumor tissue has a high prognostic efficacy in renal cell carcinoma metastasis and as a protective factor that prevents tumor progression.